Analisis Sifat Individualisme Karyawan Pada PT X - Nurvanny Agustyana; Christian Wiradendi Wolor; Adnan Kasofi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study aims to analyze the impact of employee individualism on team dynamics at PT X. The research method used is descriptive analysis with a qualitative approach. The findings show that the high level of individualism among PT X employees leads to limited collaboration and communication between team members, with most employees preferring to work independently. This reduces face-to-face interactions and hampers team synergy. However, the company is making efforts to address this issue by providing communication training, team-building activities, and collaborative work schemes across divisions. These efforts are expected to improve team effectiveness and foster a more collaborative work culture. The conclusion of this study is that high individualism negatively impacts team dynamics at PT X. To improve team dynamics, it is essential for PT X to continue promoting collaboration and communication among employees through a more open and integrative approach.